2023
DOI: 10.3390/separations10020065
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Extraction of Flavonoids from Lotus Leaves by Ultrasonic-Assisted Deep Eutectic Solvent Extraction and Its Evaluation on Antioxidant Activities

Abstract: The discovery of a green extraction solvent for natural plants could promote related research. In this study, deep eutectic solvents (DES) were used as green solvents coupled with an ultrasound-assisted extraction method (UAE) to extract flavonoids from lotus leaves. Thirty-four different DES were performed and choline chloride/urea with 40% water was chosen as the most promising one, and the related parameters in the procedures were optimized, resulting in the highest extraction amount of flavonoids in lotus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…The results revealed that DESs based on choline chloride (choline chloride/ethylene glycol and choline chloride/urea) extracted a higher amount of CBD, 0.87% and 0.78%, respectively, than ethanol (0.69%), the organic solvent most used in hemp extraction. These findings are consistent with those of Liu et al [23] in which DESs with choline chloride/urea extracted the highest amount of flavonoids from lotus leaves. However, these findings are contrary to those of Tiago et al, in which they observed a large amount of CBD extracted using menthol/lauric acid [19].…”
Section: Discussionsupporting
confidence: 93%
“…The results revealed that DESs based on choline chloride (choline chloride/ethylene glycol and choline chloride/urea) extracted a higher amount of CBD, 0.87% and 0.78%, respectively, than ethanol (0.69%), the organic solvent most used in hemp extraction. These findings are consistent with those of Liu et al [23] in which DESs with choline chloride/urea extracted the highest amount of flavonoids from lotus leaves. However, these findings are contrary to those of Tiago et al, in which they observed a large amount of CBD extracted using menthol/lauric acid [19].…”
Section: Discussionsupporting
confidence: 93%
“…Increasing the water ratio in DES-1 from 20 to 50% led to an important improvement in the extraction yield of NA. The high extraction yield may have been achieved because DES-1 viscosity and polarity were optimized by adding water, resulting in more effective interactions between ST and DES-1 ( 43 , 44 ). Yet, the extraction efficiency dropped dramatically when the water content was brought up to 50%.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed earlier, the molar ratio of HBD to HBA in the DES controls the hydrogen bonding interaction, which affects the viscosity and surface tension of DES (43). As a result, optimizing the mass transfer rate and processing efficiency relies on selecting appropriate water content in DES.…”
Section: Impact Of Water Content In Des On Na Extractionextractionmentioning
confidence: 99%